Cancer patients' use of primary care out-of-hours services: a cross-sectional study in Norway - Camilla Kjellstadli Thoresen; Hogne Sandvik; Steinar Hunskaar (Taylor & Francis Group, 2016)
Objective: To investigate how cancer patients in Norway use primary care out-of-hours (OOH) services and describe different contact types and procedures. Design: A retrospective cross-sectional registry study using a billing registry data source. Setting: Norwegian primary care OOH services in 2014. Subjects: All patients' contacts in OOH services in 2014. Cancer patients were identified by ICPC-2 diagnosis. Main outcome measures: Frequency of cancer patients' contacts with OOH services, contact types, diagnoses, procedures, and socio-demographic characteristics. Results: In total, 5752 cancer patients had 20,220 contacts (1% of all) in OOH services. Half of the contacts were cancer related. Cancer in the digestive (22.9%) and respiratory (18.0%) systems were most frequent; and infection/fever (21.8%) and pain (13.6%) most frequent additional diagnoses. A total of 4170 patients had at least one cancer-related direct contact; of these, 64.5% had only one contact during the year. Cancer patients had more home visits and more physicians' contact with municipal nursing services than other patients, but fewer consultations (p < 0.001). Patients in the least central municipalities had significantly more contacts than more central municipalities (p < 0.001). Conclusion: There was no indication of overuse of OOH services by cancer patients in Norway, which could indicate good quality of cancer care in general.KEY POINTS   Many are concerned about unnecessary use of emergency medical services for non-urgent conditions. • There was no indication of overuse of out-of-hours services by cancer patients in Norway. • Cancer patients had relatively more home visits, physician's contact with the municipal nursing service, and weekend contacts than other patients. • Cancer patients in the least central municipalities had relatively more contacts with out-of-hours services than those in more central municipalities.